2005
DOI: 10.1143/jjap.44.6833
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Dye Fluorescence by Gold Nanoparticles: Analysis of Particle Size Dependence

Abstract: Rose Bengal was spun on spherical gold nanoparticles immobilized on a quartz plate by a silane coupling agent. The enhancement of the dye fluorescence was studied by changing the diameter of the gold nanoparticles from 20 to 250 nm. A maximum enhancement of dye fluorescence was observed at a size of 100 nm. We found good agreement between the experimental result and the theoretical calculation. From the theoretical analysis it is suggested that the maximum enhancement is obtained when the incident light and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 20 publications
(32 reference statements)
1
50
0
Order By: Relevance
“…Localized plasmons are the collective oscillations of free electrons in metal nanoparticles [16,17]. When a metal nanoparticle is excited with an optical beam, electric field is formed in the particle and the electrons are transported collectively with respect to the fixed positive charges.…”
Section: Principle Of Operation and Design Of Localized Plasmonic Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Localized plasmons are the collective oscillations of free electrons in metal nanoparticles [16,17]. When a metal nanoparticle is excited with an optical beam, electric field is formed in the particle and the electrons are transported collectively with respect to the fixed positive charges.…”
Section: Principle Of Operation and Design Of Localized Plasmonic Metmentioning
confidence: 99%
“…Metal-enhanced luminescence is based on the interactions between the emission of the luminescent material and surface plasmons (or localized plasmons); in general, there are three basic mechanisms that influence the luminescence of materials close to metal films, metal structures, or metal particles [6][7][8][9][10][11][12]17]: 1.) Highly localized electric field in the near-field of the metal particles, which causes luminescence enhancement if the excitation wavelength is close to the plasmon resonance wavelength, 2.)…”
Section: Experimental Characterization and Theoretical Analysis Of Lomentioning
confidence: 99%
“…The increase of the emission intensity can be caused either by enhancement of absorption rate or enhancement of the radiative rate of the fluorophore, as well as by a combination of both processes. This effect has been in recent years observed for a variety of systems including organic dyes [6][7][8][9], semiconductor nanocrystals [10][11][12][13][14], conjugated polymers [15][16][17], DNA [18], and naturally evolved biological complexes [19][20][21]. One of the most important requirements for achieving strong enhancement of the fluorescence intensity concerns is spectral matching between the plasmonic nanoparticles and fluorophores, while at the same time the strength of the interaction depends on the separation between the two components.…”
Section: Introductionmentioning
confidence: 91%
“…Metal nanoparticles (NPs) have been extensively studied for various uses, such as ultrasensitive bio/chemical detection using fluorescence enhancement (1)(2)(3)(4)(5)(6) and/or surfaceenhanced Raman scattering. (7)(8)(9)(10)(11)(12)(13) Silver NPs are known to exhibit high enhancement whereas gold NPs have been widely used owing to their chemical stability and affinity to biochemical substances.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the nanostructures of metal NPs strongly affected the enhancement of fluorescence signals (SEF) and Raman signals (SERS) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(20)(21)(22)25) though the mechanisms of SEF and SERS are not yet conclusive. This work is dedicated to demonstrate a bottom-up manufacturing process of silver and gold NPs that can regulate the formation of silver NPs by gold NPs deposited in advance.…”
Section: Introductionmentioning
confidence: 99%